INTEGRATION OF LUMIO BY SMART PLATFORM IN THE DISCOVERY LEARNING MODEL TO IMPROVE STUDENTS CRITICAL THINKING SKILLS IN ECONOMICS SUBJECTS - Hayyun Muhayya Hanif; Armiati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2025)
The limited development of students critical thinking skills in Economics education highlights the need for more interactive and student-centered learning approaches. This study investigates the effectiveness of discovery learning enhanced with interactive digital media using the Lumio by SMART platform in improving students critical thinking abilities, compared to traditional instrctional methods. A quasi-experimental design was applied, involving all grade XI Economics students at SMAN 1 IV Koto. Total population sampling was used, with participants randomly assigned into experimental and control groups through a digital randomization tool. Class XI Economics 1 was designated as the control group and received conventional instruction, while class XI Economics 2, as the experimental group, was traught using discovery-based learning supported by multimedia interactive tools. The results showed a statistically significant improvement in the critical thinking skills of the students in the experimental grup compared to those in the control group. These findings suggest that integrating discovery learning with digital interactive media using the Lumio by SMART is an effective stategy for enhancing critical thinking in Economics education